Predictors and outcome of organizational cynicism and themoderated mediating effect of perceived organizational support among nurses in Pakistan - Munir, Yasin (2015)
Over the years, researchers in the field of management have tried to explore the factors of negative attitudes among healthcare services staff. However, related studies in the context of organizational cynicism are limited. Thus, it is essential to investigate the factors and outcomes of organizational cynicism among the healthcare services staff. The current study aimed to establish the relationship of perception of ethical climate, horizontal violence and authentic leadership style as predictors and turnover intention as an outcome of organizational cynicism along the moderated mediating effect of perceived organizational support in the nursing profession. The study used a quantitative research design, and eight hundred and seventy questionnaires were distributed to collect data from nursing staff working in Punjab region of Pakistan using a non-probability multistage sampling technique. Exploratory factor analysis (EFA), confirmatory factor analysis (CFA), multivariate data normality tests, descriptive statistics and structural equation modeling (SEM) were applied to analyze the data. The results revealed a statistically significant direct relationship among the perceptions of ethical climate, horizontal violence, authentic leadership style, organizational cynicism and turnover intention. Subsequently, results showed the full mediating effect of organizational cynicism between perception of ethical climate and turnover intention while no mediation was found between horizontal violence and turnover intention. Additionally, results indicated a partial mediating effect of organizational cynicism between authentic leadership style and turnover intention. On the contrary, moderated mediating relationship of perceived organizational support could not proceed because of the insignificant mediating effect of organizational cynicism between horizontal violence and turnover intention. Findings of the current study contributed to the literature of organizational behavior by exploring the factors and outcomes of cynicism among healthcare services staff. The study has also practical implications for nursing managers and the Ministry of Health, Pakistan as the findings would enable them to understand the factors which directly or indirectly affect the negative attitudes among healthcare services staff.